KONSEP EVALUASI PENGEMBANGAN BAHAN AJAR - Maslani, Maslani; Agnes Nuraeni Muslim; Chintia Nabilah; Cucu Komariah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Evaluation of the development of teaching materials is an important aspect in education to ensure that the material presented is effective, relevant and can improve the quality of learning. This research discusses the main concepts in evaluating the development of teaching materials, including definitions, objectives, methods and evaluation techniques that can be used. The aim of this research is to determine aspects of writing, namely including aspects of content (knowledge, skills and attitudes or values), aspects of learning methods, aspects of illustration and aspects of graphic elements. This research uses the literature review method for qualitative research, namely collecting data by reviewing literature to draw conclusions about the research object in the data collection process, namely in the form of documented notes related to text descriptions of material in student books.